Employee Work Discipline at the Baraka District Office, Enrekang Regency - Pirda, Pirda; Akib, Haedar; Nasrullah, Muh. (ASHA Publishing, 2024)
This study aims to find out the work discipline of employees at the Baraka District Office, Enrekang Regency. By using qualitative research methods with descriptive research types. The data collection technique uses observation, interview, and documentation methods. The data analysis techniques used are data collection, data presentation, data condensation and conclusion/verification. The results of the study show that each indicator used can be said to be